Sbaja a novel foliar applied growth and yield enhancer in Malaysia - Shafiee, Mohd Izzat; Baki, Burhanuddin A.; Khandaker, Mohammad Moneruzzaman; Mispa, Muhammad Shakirin; Bakar, Baki; Boyce, Amru Nasrulhaq; Saad, Johari M.; Aziz, Tengku Abdul (Universidade Federal de Uberlandia, 2018)
Product efficacy testing during 2006 to 2010 with SBAJA (a novel scientifically formulated foliar-spray growth and yield enhancer) in the greenhouse and multi-location field trials registered measurable increase in chlorophyll contents, robust and healthier crop growth and increased yield and biomass production. In field trial, rice plants receiving normal NPK fertilizer at the rates of 100:50:30 served as control and spray treated with SBAJA at 40 and 60 days after sowing (DAS). All the experiments were laid out in Randomized Complete Block (RCB) Design and replicated five times. Tiller number and panicle characteristics; length, weight, number of grains, number of filled grains were significantly increased with 1:300 SBAJA treatment. In addition, 1000 grain weight and rice yield increased significantly with SBAJA treatments. Normal fertilizer applications in field trials augmented with SBAJA in 2008-2010 in the Selangor North West Project (SNWP), registered measurable increase in rice yields by 25-30% from 6.2-6.5 tons/ha to 7.8-8.9 tons/ha. It is concluded that foliar spraying with SBAJA at 40 and 60 days after sowing increased growth and yield of rice under green house and field conditions.